Editorial - Editor (Dr. Chinmay Pandya, 2016)
The journey of Dev Sanskriti In1erdisciplinary International  Journal  (DSIIJ)  is  entering  into  a new year and we take this privilege to wish each one of you a happy and peaceful year ahead. May we all scale new spiritual heights and continue striving forward in in1egrating Science and Spirituality. In this edition we bring you scholarly works from different streams offering a wide spectrum of spiritual and scientific learning. Ranging from physical and emotional health to cinema, from the identity of Indian woman portrayed by soap operas to the key features of Indian Psychology, from smart cities to heritage cities, the art of writing to the therapeutic effects of black pepper, from Universal brotherhood, to Human Resource Management in the light of teachings of Swami Vivekananda, and environmental  orientation  in the divine writings of famous poet and devotee Surdas; this edition is going to surely bring our understanding to new heights. While the world faces an increase in the number of people suffering with asthma, and the modern medicinal inventions fall short of the expected   results.   Dr.   Avnish   Kumar   &  Dr. Kaushal Kumar draw our attention to Ethno medicinal & Ayurvedic approach in the management and treatment of Asthma. Among  the  International   contributions, Dr. Roxanne Henkin et a!., share their reflections and insights on the reaching of writing. Indian  women  hold  a  strong  command and respect in the international fraternity. While the soap operas of Indian television project them in a different way, what is the true identity of an Indian woman? How does the Indian soap opera project  Indian  women  and  what  are  the implications of those myths and ideologies? Ms. Saraswati Das has dwelled upon these questions in an attempt to exhibit the identity of Indian women as portrayed on Indian television. Human  resource  is  the  key  to  run  any organization. In the present day world, when the organizations are failing to manage human resources and align them towards a larger goal. Our next research paper explores the teachings of Swami Vivekananda - the ideals of sraddha, love, compassion, renunciation of power, tolerance, positive thinking and swahridayta in Kapil K. Bhattacharyya's paper. The goal of human life is to attain salvation. Each one of us is striving hard for happiness while dealing with our day to day challenges. Our own mind confuses us and sometimes even betrays us. Positive psychology is  a  relatively   new  field  that  examines  how ordinary people can become happier and more fulfilled. Indian psychology is an approach based on Indian ethos. Dr. Priyanka attempts to explain how both Positive and Indian psychologies focus on human happiness, their unique strengths, and how the goals of Positive psychology can be achieved through Indian spiritoal heritage. The  Indian  government  is  campaigning for smart cities and working hard for a glorified future. Indian history also enjoys a rich heritage in its towns and cities. Ancient Indians had a well planned system of building villages and towns which is evident from archeological and li1erary sources. They had different designs and features with intricate drainage, water supply systems, markets, palaces, households and public spaces. Dr. R. Suresha, offers a glimpse of ancient Indian town planning for building modem smart cities With  the  objective  to  bring  forth  the knowledge and information about Maricha (black pepper) in our classical1exts, Dr. Bhavna Singh highlights the synonyms, pharmacodynamics, therapeutic actions, uses, and the different formulations of Maricha as described in ancient Ayurvedic     literature    like    Brihat    trayi     and Nighantus. With what outlook should one construct, analyze, or dissect film theory? Should one view cinema as a medium of mass communication? Propaganda? Entertainment? Art?  Or  should cinema be considered a concoction of them all? In trying to formulate a film theory that deals with all these elementary characteristics poses a serious problem. Soumik Chatterjee advocates that it should be required for Indian cinema to be able to provide at least a level of generalization in answering the aforementioned questions, to be considered to have a theory of its own. This paper is an attempt to investigate whether or not such a generalization (subsequently, a film theory) is possible for Indian cinema, and then to find out how much of that theory is rooted in our original outlook towards the audio-visual art. In  a  unique  attempt,  Dr.  Sujata Chaturvedi explores the orientation and care for environment  in  the  divine  writings  of  famous poet Surdas, through the example of Krishna-leela playing with animals and plants. The feeling of nationalism connects individuals  together  and  as  a  result  it  reduces crime, distrust,  fights,  unrest,  etc. In the olden days, this was common and hence universal brotherhood was a common phenomenon. The Indian texts defme the Sanskrit term shastra as Universe, not confined to a single nation. Dr. Indresh Pathik attempta to offer a solution to the present day problems by propagating this golden concept  of  universal  brotherhood  through  his paper. We would  like  to  whole-heartedly congratulate and thank all the contributors and reviewers. We hope this issue will inspire and generate interest among researchers, educators, policy makers and professionals to understand the significance   of   indigenous  knowledge   in   the present era. We would also like to thank  all our readers  and  seek  your  feedback  to  make  this journal a more effective vehicle of indigenous knowledge.